2021
DOI: 10.1186/s12889-021-12100-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of intimate partner violence and other risk factors with HIV infection among married women in India: evidence from National Family Health Survey 2015–16

Abstract: Background Human immunodeficiency virus (HIV) infection remains an important public health concern in many countries. It is fuelled by gender inequality and disparity, which has resulted in a fundamental violation of women’s human rights. This study aims to find out the association of intimate partner violence (IPV) and other risk factors with the prevalence of HIV infection among married women in India. Methods This study is based on data from the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
2
4
0
Order By: Relevance
“…Similar findings have been reported by [43] in a study of IPV among men with Physical disabilities [43], among men with mental health challenges by [44], and among men who abuse alcohol [45]. Though the reasons for victimization may vary as noted above, it is generally presumed that men living with HIV like women living with HIV, experience violence as a result of discrimination [46][47][48]. Though, it is possible that some women show their discontent to their partners for infecting them with HIV by resorting to violence, while others use violence to settle grievances between them and their partners.…”
Section: Discussionsupporting
confidence: 79%
“…Similar findings have been reported by [43] in a study of IPV among men with Physical disabilities [43], among men with mental health challenges by [44], and among men who abuse alcohol [45]. Though the reasons for victimization may vary as noted above, it is generally presumed that men living with HIV like women living with HIV, experience violence as a result of discrimination [46][47][48]. Though, it is possible that some women show their discontent to their partners for infecting them with HIV by resorting to violence, while others use violence to settle grievances between them and their partners.…”
Section: Discussionsupporting
confidence: 79%
“…Similar findings have been reported by [43] in a study of IPV among men with Physical disabilities [43], among men with mental health challenges by [44], and among men who abuse alcohol [45]. Though the reasons for victimization may vary as noted above, it is generally presumed that men living with HIV like women living with HIV, experience violence as a result of discrimination [46][47][48]. Though, it is possible that some women show their discontent to their partners for infecting them with HIV by resorting to violence, while others use violence to settle grievances between them and their partners.…”
Section: Discussionsupporting
confidence: 64%
“… 17 The authors’ findings on the role of ACEs, perinatal substance abuse and HIV against IPV are consistent with other major studies. 2 , 18 , 19 …”
Section: Discussionmentioning
confidence: 99%
“…17 The authors' findings on the role of ACEs, perinatal substance abuse and HIV against IPV are consistent with other major studies. 2,18,19 The lack of significant findings against sexual violence warrants further discussion. A previous study by Kidman and Violari 20 showed that ACEs, substance use during pregnancy and HIV were significantly associated with sexual IPV.…”
Section: Discussionmentioning
confidence: 99%